A catalogue of Limacodidae (Lepidoptera: Zygaenoidea) from India - Ahmad, Jalil; Irungbam, Jatishwor Singh; Solovyev, Alexey V.; Giusti, Alessandro; Joshi, Rahul; Singh, Navneet (Zootaxa, 2025)
A total of 195 species belonging to 80 genera of Limacodidae are catalogued from India, including 3 newly recorded species: Altha (Belgoraea) rufescens Swinhoe, 1893, Belippa ochreata Yoshimoto, 1994, and Prapata bisinuosa Holloway, 1990. The genus Miresa Walker, 1855 is the most diverse genus in India, representing 10 species, followed by Parasa Moore, in Horsfield & Moore (1858–59) with 9 species, and Scopelodes Westwood, 1841 with 8 species. Of the 80 genera documented, 39 are monotypic. A comprehensive series of data on the diversity of Indian Limacodidae, with information on type species, type localities, synonyms, and distribution in different parts of India as well as global records, are provided.